Kiai's Spiritual Leadership (Multi-Site Study At Purba Baru Musthafawiyah Islamic Boarding School, Mandailing Natal Regency, And Al Jamaliyah Raso Islamic Boarding School, Central Tapanuli Regency) - Lubis, Mhd Syahdan; Wijaya, Candra; Mardianto, Mardianto (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The aim of this research is to discuss spiritual leadership at the Musthafawiyah Purba Baru Mandailing Natal Islamic Boarding School and the Al Jamaliyah Raso Islamic Boarding School, Central Tapanuli. This research uses a multi-site qualitative method where data collection techniques include interviews, observation, and document study techniques. Meanwhile, to strengthen the validity of the data findings and the authenticity of the research, the researcher refers to the use of data validity standards suggested by Lincoln & Guba, which consist of credibility, transferability, dependability, and confirmability. The results of this research are: 1). The values adhered to by Kiai at the Musthafawiyah Purba Baru Islamic Boarding School in Mandailing Natal and the Al Jamaliyah Raso Islamic Boarding School in Central Tapanuli are some of the values that are implemented in the behavior of Kiai or Islamic boarding school caregivers every day. Namely, the application of the values of honesty, justice, the spirit of good deeds, and discipline. The attitudes and behavior of Kiai at the Musthafawiyah Purba Baru Islamic Boarding School in Mandailing Natal and the Al Jamaliyah Raso Central Tapanuli Islamic Boarding School have the attitude and behavior of guiding, directing, encouraging, and moving their subordinates to achieve a desired goal; and 3). Kiai's efforts to improve spiritual leadership at the Musthafawiyah Purba Baru Mandailing Natal Islamic Boarding School and the Al Jamaliyah Raso Central Tapanuli Islamic Boarding School involve implementing classroom learning like madrasas in general, then applying the halaqah concept and implementing the hidden curriculum.